Capitalism XXL : why the global economy became gigantic and how to fix it - Noels, Geert, 1967- (McGill-Queen's University Press, 2023)
"Our world is suffering from economic gigantism. Under the current capitalist system huge companies and organizations are becoming even larger and more powerful, creating a Champions League effect that kills healthy competition, doesn't consider sustainable growth, and leaves workers feeling pressured and susceptible to burnout. Capitalism XXL makes it clear that current rules of capitalism favour bigness in an unfair way, and that a general unease with the capitalist system is growing. The trend for bigness goes beyond businesses: schools, hospitals, libraries, and all kinds of organizations, misled by economies of scale, have consolidated. A larger entity can seem attractive for its short-term financial gains, but the results produce enormous social costs. Rather than dismantling the capitalist system in favour of neo-Marxism, Geert Noels argues, we have to instead go back to the roots of capitalism and embrace its traditional principles as written by Adam Smith in the eighteenth century. Capitalism XXL makes the case for changing the rules in order to tame the giants and restore the individual to the world economy. Guided by history, Noels proposes an approach to capitalism that considers all human dimensions--social, ecological, and economic--and describes a sustainable future economy that will not burden the generations to come with debt, social inequality, and a natural environment that is damaged beyond repair."--